PENERAPAN MODEL PEMBELAJARAN LESSON STUDY PRAKTIKUM WISATA UNTUK MENINGKATKAN PENGUASAAN KONSEP DAN BERPIKIR KREATIF SISWA KELAS X SMA N 1 LANGGAM PELALAWAN - Jurniati Jurniati (Jurnal Geliga Sains: Jurnal Pendidikan Fisika, 2009)
This study aimed to explore the use of Lesson Study model of learning physics lab tours in SMANegeri 1 Langgam. Physics of matter to be discussed is the temperature and heat. Samples selectedexperimental class X consisting of 30 persons of SMA N 1 Langgam Pelalawan regency of Riau. Used forcomparative learning models (conventional) are also given to the class X pilial class at the same high school,with student numbers by 28 people. Experimental studies focused on (1) conceptual tests in the form of anobjective test, (2) tests of creative thinking skills, and (3) a questionnaire to explore the response of studentsand teachers to the learning model Lesson Study Tour Practice and its use. The results showed that the use oflearning models Lesson Study Tour Practice can significantly further improve the mastery of concepts andcreative thinking skills of students compared with the use of conventional learning models. Teachers andmost students responded positively to the use of models Lesson Study Tour Practice in teaching physics inschool. They get excited and motivated to an active role in the learning process, they felt their teamwork andcommunication skills both orally and in writing can be trained, they also feel the understanding of conceptsand thinking skills can be facilitated, and most of them want to use this learning model.